Cultural heritage from the perspective of the World Tourism Organization - Paredes Izquierdo, Juan Carlos (2018)
The purpose of this paper is to help build bridges of dialogue between the cultural sector and the tourism sector, or more specifically, between professionals and institutions responsible for the conservation and management of cultural heritage, and professionals and institutions responsible for tourism management. To this end, it seeks to demonstrate the importance that the World Tourism Organization grants to cultural heritage, not only as a tourist resource, but also as a fundamental element for the identity of communities and for the achievement of a sustainable development, in accordance with the United Nations Sustainable Development Goals. To attain this, we use various sources, documents and reports that show this particular perspective from the field of tourism.